A NOVEL SYNTHETIC ROUTE FOR SUPPORTING RUTHENIUM COMPLEXES ON FUNCTIONALIZED SILICA-GEL - Neiva, SMC; Santos, JAV; Moreira, J. C.; Gushikem, Y.; Vargas, H.; Franco, D. W. (Amer Chemical Soc, 1993)
The immobilization of the ruthenium moiety Ru(NH3)4SO3 by reaction of trans-[Ru(NH3)4SO2(H2O)]2+ with silica gel functionalized with 3-(1-imidazolyl)propyl groups is reported. A 60% surface coverage was obtained in the proportion of the resulting material [=Si(CH2)3imN-Ru(NH3)4SO3]. The anchored Ru(II) complex was characterized and its reactivity investigated. Derivatives of CO, pyrazine, and isonicotinamide have been prepared and characterized by electronic and vibrational spectroscopies, as well as by chemical means. The [=Si(CH2)3imN-Ru(NH3)4SO4]Cl, obtained through oxidation of the corresponding ruthenium(II) sulfite species, has been characterized and the aquo and the oxalate derivative have been synthesized.